The Role of University in Awareness of Social and Cultural Human Rights to Students (Journal of the College of Education for Women, 2019)
The role of university in awareness of Social and Cultural Human Rights to Studentsstill at the beginnings . the irritable secure of Iraqi environment is the most challenges thatcease any work that may raise the human rights in university . in spite of obstacles the samesociety of university like conferences and meetings that related to this subject . as well as theluck of professional teachers.This study raises a group of important questions, perhaps the most :The contribution of university in educates their students of the social and cultural humanrights? What are the most challenges that facing these students? Does the universityresponsible of this luck of understanding these human rights?This Study tried to highlight on the Role of university in awareness of Social and CulturalHuman Rights to Students through the following :First: The problem, the importance and the goalsSecond: Determine the scientific concepts and terms.Third: The Role of university in awareness of Social and Cultural Human Rights to Students.Finally: Conclusion.